PENGARUH PAN ISLAMISME BAGI KEKHILAFAHAN TURKI UTSMANI PADA MASA SULTAN ABDUL HAMID II - Ahmad Salman Kurniawan; Nurfitri Hadi (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 1970)
This study describes and analyzes the influence of the idea of ​​Pan Islamism in the Ottoman Caliphate during the reign of Sultan Abdul Hamid II using qualitative research methods. The framework of thinking needs to be used to explain the object of research from the core of the problem in more detail, the main problems of this research, namely: 1. The social and political conditions of the Ottoman Turks before and the beginning of the leadership of Sultan Abdul Hamid II, 2. Understanding Pan Islamism and how the process of spreading the idea of ​​Pan Islamism in the Ottoman Caliphate, 3. The influence of Pan Islamism on the Ottoman Caliphate during the reign of Sultan Abdul Hamid II. This study uses historical research methods through several stages of historical methods, such as data collection (heuristics), source criticism, interpretation and historical writing (historyography) so that a study can be carried out regularly and accurately. The theory used in this research, namely the theory of influence which is used to explain and reveal the influence of Pan Islamism in Ottoman Turkey, and also uses the theory of diffusion of innovation to describe the process of spreading the idea of ​​Pan Islamism. The results of this study indicate that Pan Islamism has an influence on the fields of education, religion, physical facilities, and especially the political field. Pan Islamism which became the political policy of Tukir Ottomans since the time of Sultan Abdul Hamid II succeeded in building support from Muslims in various regions against the Ottoman Turks. The idea of ​​Pan Islamism continued to develop in the Ottoman Empire until its collapse in 1924.